Anopheles mosquitoes New insights into malaria vectors - Manguin, Sylvie (IntechOpen, 2013)
Anopheles mosquitoes are highly important insects due to their involvement in the transmission of human malaria and its devastating consequences in endemic countries worldwide. In 2010 alone, malaria was responsible for an estimated 660,000 deaths. As the study of Anopheles species and populations is a key element for reaching the goal of malaria elimination, an enormous amount of information has accumulated over the past century, and together in recent decades with the advent of novel technologies the acquisition of new knowledge has accelerated even further. The originality of this book is to offer the latest compilation on various research, new concepts, paradigms and innovative approaches for the control of anophelines using state-of-the-art methodologies and analysis. The 24 chapters, written by internationally recognized experts from 5 continents, cover the rich landscape for the understanding of Anopheles mosquitoes and the development of more effective weapons to control the vector of malaria.